Magneto-optical properties of olive oil combined with natural turmeric powder as a dye. (May 2021) - Mousavi, Z.; Majles Ara, M.H.; Ghafary, B.; Ahanian, I.
Highlights: Verdet constant of olive oil was measured. Cotton-Mouton constant of olive oil was measured experimentally for the first time. Turmeric dye is used to enhance the magneto-optical properties of Olive oil for the first time. Olive oil & its dye blended are novel natural materials for magneto-optical applications and sensors. Abstract: In this research, magneto-optical properties of olive oil as a pure liquid and also mixed with turmeric powder at diverse concentrations as a dye, are figured out experimentally. The modified nulled intensity method was applied to measure Verdet and Cotton-Mouton constants of pure olive oil and the blended mixtures. The Verdet and the Cotton-Mouton constants of olive oil were calculated to be 101.05 deg Tm and 77.96 1 T 2 m, respectively. The Cotton-Mouton constant of olive oil was reported for the first time according to the authors' information at low magnetic field strength. Adding turmeric to olive oil enhances the magneto-optical properties of the material. The results demonstrate the mentioned samples are novel materials for magneto-optical applications.